2022
DOI: 10.1515/multi-2022-0062
|View full text |Cite
|
Sign up to set email alerts
|

Children’s use of English as lingua franca in Swedish preschools

Abstract: This paper highlights a current phenomenon reported from preschools placed in multilingual areas in Sweden, namely that some preschoolers with mutually different language backgrounds sometimes use English as lingua franca instead of Swedish during play. The data stems from a study of language environments in Swedish preschools situated in both monolingual and multilingual areas. The analyses reveal that many children are influenced by the English language in both areas, but to a much greater extent in multilin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
0
1
0
1
Order By: Relevance
“…Teachers in Swedish preschools have observed that some children, particularly those with weak Swedish proficiency, often use English to communicate with one another and sometimes even with teachers when they have a difficult time making themselves understood in Swedish. A recent study of this phenomenon has shown that children in Swedish preschools located in multilingual areas use English and not Swedish as a lingua franca, even though teachers communicate with them in Swedish (Larsson et al., 2023). Even some children as young as 3 use English for different purposes.…”
Section: The Domains and Functions Of English In Swedenmentioning
confidence: 99%
“…Teachers in Swedish preschools have observed that some children, particularly those with weak Swedish proficiency, often use English to communicate with one another and sometimes even with teachers when they have a difficult time making themselves understood in Swedish. A recent study of this phenomenon has shown that children in Swedish preschools located in multilingual areas use English and not Swedish as a lingua franca, even though teachers communicate with them in Swedish (Larsson et al., 2023). Even some children as young as 3 use English for different purposes.…”
Section: The Domains and Functions Of English In Swedenmentioning
confidence: 99%
“…Children's role play or so-called sociodramatic play, where participants take on various social roles within a dynamically changing play script, is considered a key social activity that is conducive to learning and the development of social skills and sociocultural knowledge (Corsaro, 2015;Vygotsky, 1978). Sociodramatic play is a notably complex activity requiring social, linguistic, and communicative skills to be able to participate creatively and on an equal footing (Garvey, 1990;Larsson et al, 2022). According to the Scandinavian pedagogical model, play takes up a large part of the time children spend in preschool, and play activities can be shaped and organized in various ways (Samuelsson & Asplund Carlsson, 2008).…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
“…Även om nämnda språkideologiska läroplansformuleringar kan sägas samspela med modern forskning genom synliggörandet av flera språk, omfamnar det politiskt formulerade uppdraget knappast den relationella komplexitet som flerspråkighet i reella sammanhang ofta är ett uttryck för (Martín-Bylund, 2017). Exempelvis säger läroplanen ingenting om barns användning av andra språk än modersmål, likt den enligt många förskoleverksamheter framväxande användningen av engelska, framför svenska, som ett lingua franca (Larsson et al, 2022). Detta trots att engelska beskrivs "fungera […] på många sätt som ett andraspråk för dem som växer upp i Sverige" (Isof, 2023).…”
Section: Introduktionunclassified